FAKTOR-FAKTOR YANG MEMPENGARUHI HASIL BELAJAR MAHASISWA BIDIKMISI FAKULTAS TEKNIK UNIVERSITAS NEGERI PADANG - Riska Yurnaliza; Totoh Andayono (CIVED, 2019)
Abstack - Bidikmisi students of FT UNP have learning outcomes / Achievement Index below the provision standard of Bidikmisi UNP (2.5) 60 people, therefore it is necessary to know the reasons. The type of this research is  quantitative descriptive research, data  collection techniques is  using questionnaires. The population of this research is Bidikmisi students of Education Study Program of FT UNP 2015-2018, amounting to 392, to determine the quantity of samples the Taro Yamane formula is used, so 80 people samples are obtained. Data analysis techniques is by using percentage calculations performed by calculating the frequency of respondents' answers on each sub-indicator of the study. Based on the results of the research that has been done, it can be concluded that the results of the study shows the factors that most influence the learning outcomes of FT UNP’s Bidikmisi students from external factors are the family with the highest achievement score of 85.81% while the lowest score is 64,21% from the surrounding environmental factors, this shows that the family environment is quite encouraging so that students get good learning outcomes while the surrounding environmental not affected for the learning outcomes of Bidikmisi students of FT UNP. Keywords: Result Of Study, Bidikmisi